The Socioecological Model as a framework for exploring factors influencing childhood immunization uptake in Lagos state, Nigeria - Abisola Olaniyan; Chinwoke Isiguzo; Mary Hawk (BMC, 2021)
Abstract Background Nigeria is one of the ten countries globally that account for 62% of under- and unvaccinated children worldwide. Despite several governmental and non-governmental agencies' interventions, Nigeria has yet to achieve significant gains in childhood immunization coverage. This study identifies intrapersonal, interpersonal, organizational, community, and policy-level factors that influence childhood immunization uptake from various stakeholders' perspectives using the Socioecological Model (SEM). Methods Using the Socioecological Model as a guiding framework, we conducted ten focus group sessions with mothers/caregivers and community leaders residing in Lagos state and nine semi-structured interviews with healthcare workers who provide routine immunization services in Lagos state primary healthcare facilities. We performed a qualitative analysis of focus groups and semi-structured interviews using deductive coding methods. Results The study sample included 44 mothers/caregivers and 24 community leaders residing in Lagos State, Nigeria, and 19 healthcare workers (routine immunization focal persons) working in the primary healthcare setting in Lagos state. Study participants discussed factors at each level of the SEM that influence childhood immunization uptake, including intrapersonal (caregivers' immunization knowledge, caregivers' welfare and love of child/ren), interpersonal (role of individual relationships and social networks), organizational (geographical and financial access to health facilities, health facilities attributes, staff coverage, and healthcare worker attributes), community (community outreaches and community resources), and policy-level (free immunization services and provision of child immunization cards). Several factors were intertwined, such as healthcare workers' education of caregivers on immunization and caregivers' knowledge of vaccination. Conclusions The reciprocity of the findings across the Socioecological Model levels emphasizes the importance of developing multi-pronged interventions that operate at multiple levels of the SEM. Our results can inform the design of culturally appropriate and effective interventions to address Nigeria's suboptimal immunization coverage.